Radiation heat transfer enhanced absorber for high temperature solar-thermal applications. Issue 8 (June 2016) - Fang, Zhenggang; Lu, Chunhua; Lu, Yi; Ma, Delin; Wei, Ling; Li, Peiwen; Ni, Yaru; Tao, Shunyan; Xu, Zhongzi
Abstract: A novel design of a solar absorber making use of different optical properties of materials for high temperature solar-thermal applications is proposed. For the two sides of the sample, the solar absorbing surface is designed to absorb sunlight and reduce radiative heat loss, while the high emission surface is aimed at enhancing the heat transfer. The composite samples were prepared by tape casting, alternately laminating and high temperature sintering. Room temperature optical properties and temperature-dependent radiative properties of the composite samples were studied. The results showed that the emittances of the absorbing surface and heat transfer surface were 0.32 and 0.70, respectively. Due to this difference of emittances, the two surfaces exhibited a radiation temperature (read from thermography camera) difference of 140 °C when the actual sample temperature is 600 °C.